Telecommunications network design: Technology impacts and future directions. Issue 2 (16th October 2020) - Wong, Richard T.
Abstract: During the past 50 years telecommunication network technology has raced ahead powered by exponential advances in computer chip and fiber optic technology. The introduction of packet‐switched networks and the Internet has increased network traffic demands exponentially and has nurtured a variety of new telecommunication services (e.g., email, web‐surfing, social media, streaming services, e‐commerce, the Internet of Things, etc.) over the past 30 years. This rapidly changing environment (along with certain technical considerations) has made it very difficult to give accurate forecasts of traffic demands for both the short‐term (intraday) and for the longer term (year‐to‐year). Telecommunications network design has evolved from the voice‐only networks of the 1970s where operations research (OR) methodology was indispensable to current multiservice packet‐switched data networks whose uncertainty and rapid evolution has reduced the utility of classical optimization models that rely on accurate traffic demand forecasts. After summarizing the major developments in telecommunications network design technologies/services, we describe some promising future research directions to address an environment where technology is ever‐changing and traffic forecasting is difficult. In particular, we focus on the public Internet and emphasize possible work where OR/optimization methodology may be useful in understanding and solving telecommunications network routing and design problems.